Assessing Sierra Leone's Consumption Function: A Cointegration and an Error Correction Model Approach - Ibrahim Abubakarr Bah (ZBW - Leibniz Information Centre for Economics, 2022)
This study uses Cointegration and an Error Correction Model to investigate the responsiveness of household consumption to changes in income in Sierra Leone covering the periods 1980 to 2020. The study relies on annual time series data on consumption and gross domestic product from the World Bank's World Development Indicators database. In the empirical model, consumption depends entirely on income. The results show that in the short-run, 85 percent of additional income goes toward consumption and that income is greater than consumption in the short-run with an adjustment value of 75 percent annually. In the long-run, the results show a significant marginal propensity to consume of 1.02 meaning that an additional 1 Leone is fully put into consumption. The long-run marginal propensity to consume does confirm results from previous studies that show relatively higher marginal propensities to consume in the long-run for low-income countries compared to middle- and high-income countries. An important policy implication of this study is that any increase in spending by the government to boost aggregate demand can also significantly increase consumption.
Keywords: 330; Marginal Propensity to Consume; Consumption; Income; Cointegration; Error Correction Model; Sierra Leone